Sex determination from different sternal measurements: A study in a Thai population - Saw Myint tun (2018)
© 2015 Anatomical Society of India. Introduction: Estimation of sex is an important initial step for personal identification of unknown skeleton remains in forensic investigation. The aim of the present study was to evaluate the applicability of the sternum for sex estimation of adult skeletal remains by measuring the sternum of Thai individuals. Methods: A study of 281 adult Thai dry sterna with known sex (192 males and 89 females) was carried out for sexing by using measurements. Discriminant function analysis was used. Results: The results showed that all parameters included in this study were significantly sexually dimorphic except sternal width index. By using discriminant function analysis, it was observed that the best parameter was the combined length of manubrium and mesosternum yielded cross-validated sex allocation accuracy rate 85.8% (82.4% for male and 95.7% for female), followed by sternal area with classification accuracy rate 82.9% (79.2% for males and 91.2% for females) and the length of mesosternum with classification accuracy rate 81.1% (78.8% for males and 88% for females). A stepwise discriminant function, which included 5 linear measurements from both manubrium and mesosternum yielded highest classification accuracy rate of 86.4%. Discussion: The results of the present study proved that the sternum is a reliable element for sex determination in Thai population and it may be a useful tool in forensic investigations.